Test of Various Mole Concentrations of Bamboo Shoots on the Production of Large Chili (Capsicum annum L.) - Hadi Suhardjono; Ida Retno Moeljani; Guniarti (Future Science, 2021)
The aim of this study was to determine the effect of giving MOL bamboo shoots and to find out the pattern of similarities due to the MOL concentration of bamboo shoots on the growth and yield of large chili plants. The study used a completely randomized design (CRD) consisting of 5 treatments and 3 replications consisting of K0 (0 0/00), K1 (10 0/00), K2 (20 0/00), K3 (30 0/00), K4(40 0/00). Parameters observed were plant height, number of leaves, number of productive branches, fruitsset, number of fruits and fruit weight. The data analysis technique used analysis of variance (ANOVA) and regression to determine the pattern of equations due to concentration. The results showed: 1). Giving MOL bamboo shoots has an effect on increasing the growth and productivity of chili plants, 2). The most effective MOL concentration of bamboo shoots to increase growth and production of chili plants was 39.23 0/00.